Beasts and beauty : dangerous tales - Chainani, Soman (Harper, 2021)
Contains a collection of twelve retellings of famous fairy tales. First, the girl called Little Red Riding Hood fights back against the wolf. Next, a prince awakens to a surprising visitor. Later, Jack climbs a beanstalk and finds a father figure. Then, two siblings follow a trail through the woods after being abandoned by their father and stepmother.